1998
DOI: 10.1099/0022-1317-79-11-2709
|View full text |Cite
|
Sign up to set email alerts
|

The neutralizing antibody response against a conserved region of human immunodeficiency virus type 1 gp41 (amino acid residues 731-752) is uniquely directed against a conformational epitope.

Abstract: Amino acids 731-752 (731 PRGPDRPEGIEEEGGERD-RDRS 752 ) of the transmembrane glycoprotein gp41 of human immunodeficiency virus type 1 (HIV-1) are conserved in most virus isolates and are controversially reported to be implicated in virus neutralization. The humoral response in infected patients against this region is poor and humans immunized with gp160 show high levels of antibodies against the peptide but poor neutralization titres. Nonetheless, several groups have succeeded in obtaining neutralizing antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
(31 reference statements)
1
30
0
Order By: Relevance
“…CT reactivity. Although it is thought that the CT of gp41 is contained by the viral membrane, there are several MAbs that recognize a hydrophilic region in the so-called "Kennedy epitope" (PRGPDRPEGIEEEGGERDRDRS) at the N terminus of the CT (aa 724 to 745) (29,44). Two possible structures have been proposed for the CT, with each being adopted as part of drastic conformational changes produced by gp41 during viral infection (41,61).…”
Section: Ab Response Against Gp41mentioning
confidence: 99%
“…CT reactivity. Although it is thought that the CT of gp41 is contained by the viral membrane, there are several MAbs that recognize a hydrophilic region in the so-called "Kennedy epitope" (PRGPDRPEGIEEEGGERDRDRS) at the N terminus of the CT (aa 724 to 745) (29,44). Two possible structures have been proposed for the CT, with each being adopted as part of drastic conformational changes produced by gp41 during viral infection (41,61).…”
Section: Ab Response Against Gp41mentioning
confidence: 99%
“…1), the foreign epitope would be presented as an immunogen able to elicit antibodies reactive to the native epitope. This system, when used with the V3 loop epitope (35) and the ERDRD conformational epitope of gp41 (6), has yielded results that indicate the important role of the backbone structure of the virus both in fixing a conformation similar to the natural one and in promoting a vigorous antibody response through the heterologous context. Hence, we constructed four recombinant FHV capsid proteins expressing the CCR5 89-102 epitope.…”
Section: Discussionmentioning
confidence: 99%
“…The FHV Epitope Presenting System (6,7,32,35), based on a modified capsid precursor protein of the Flock House virus (FHV), was obtained through the courtesy of F. Baralle (ICGEB, Trieste, Italy). The system is composed of a set of five modified capsid gene sequences (cloned in the expression vector pET-3 [Novagen, Madison, WI]), in each of which the nucleotide sequence corresponding to a peptide loop was replaced by a single Bsu36I restriction site to allow the oriented insertion of a synthetic polynucleotide coding for a foreign epitope in five distinct sites (L1, L2, L3, I2, and I3) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This evidence centres on the use of neutralizing antibody specific for a highly conformational epitope with the sequence (%'ERDRD(&! (Buratti et al, 1998 ;McLain et al, 1996 a, b) (according to the numbering system of Ratner et al, 1985). We showed that (i) ERDRD-specific IgG binds free HIV-1 particles in solution and that this virus remains neutralized after unbound antibody is separated from putative virus-antibody complexes by centrifugation (by using infectivity as the readout, the problem of broken virus particles in which the epitope might be artefactually exposed was avoided) ; (ii) ERDRDspecific IgG failed to bind to protease-treated wt HIV-1 virions ; (iii) a deletion mutant lacking most of the C-terminal gp41 tail was not neutralized, implying that the epitope was present in that location ; and finally, (iv) neutralizing antibody escape mutants selected by growth of virus in the presence of ERDRD-specific antibody carried a single amino acid substitution adjacent to the epitope that eliminated the binding of the selecting antibody (S. M. Cleveland, L. McLain, T. D. Jones, C. Parry and N. J. Dimmock, unpublished data).…”
Section: Discussionmentioning
confidence: 99%